qSOFA—welcome to the sepsis alphabet soup - Hou, Peter C.; Seethal, Raghu R.; Aisiku, Imoigele P. (Journal of Thoracic Disease, 2017)
Sepsis-3 has generated a significant amount of debate and controversy since its introduction. Specifically, Sepsis-3 introduced qSOFA as a new terminology for identifying at risk patients for sepsis.